Networks of influence and power
1 online resource.
Keywords: "During the nineteenth century Liverpool became the heart of an international maritime network. As the 'second city' of Empire, its merchants and shipowners operated within a transnational commercial and financial system, while its trading connections stimulated the development of new markets and their integration within an increasingly global economy. This ground-breaking volume brings together ten original contributions that reflect upon the development of the city's business community from the early-nineteenth century to the outbreak of the First World War with an emphasis on the period from 1851 to 1912. It offers the first detailed analysis of Liverpool's merchant community within a conceptual and historiographical framework which focuses on the economic, social and cultural role of business elites in the nineteenth century. It explores the extent to which business success was predicated on the maintenance of networks of trust; analyses the importance of business culture in structuring commercial operations; and discusses the role of ethics, trust and reputation within the changing framework of the business environment. Particular attention is paid to the role of women and the important contribution of the family to commercial success and the maintenance of social networks. Changes in business practice and social networks are also examined within a spatial context in order to assess the impact of the development of a distinct commercial centre and the clustering of commercial activity on interaction, reputation and trust, while particular attention is paid to the effect of suburbanization on existing associational networks, the social cohesiveness of business culture, and the cultural identity of the merchant community as a whole"--